A framework for the principled debugging of Prolog programs how to debug non-terminating programs - Brna, Paul; Bundy, Alan; Pain, Helen (1990)
Abstract: "The search for better Prolog debugging environments has taken a number of different paths of which three are particularly important: improvements to monitoring tools (notably the Transparent Prolog Machine (Eisenstadt & Brayshaw, 1987)), providing for greater user control over the debugging process (notably as in Opium p+ s (Ducasse, 1988)), and partially automating the debugging process (notably in (Pereira, 1986; Lloyd, 1986; Pereira & Calejo, 1988; Naish, 1988)). A serious problem associated with this activity lies in providing a principled conceptual framework within which the programmer can work with a number of different debugging tools
Keywords: Computer software; Debugging in computer science; Prolog (Computer program language)